The "Sugi sakit" Ritual storytelling in a Saribas Iban rite of healing - Sather, Clifford (Wacana, Journal of the Humanities of Indonesia, 2016)
This paper describes a Saribas Iban rite of healing called the Sugi sakit. What distinguished this rite from other forms of Saribas Iban healing was that it incorporated within its performance a long narrative epic concerned with the adventures and love affairs of an Iban culture hero named Bujang Sugi. Here I explore the language used by Iban priest bards both in telling the Sugi epic and in performing the larger ritual drama in which it was set, and look, in particular, at how the Sugi epic, which was otherwise told for entertainment, was integrated into this drama and recast by the priest bards as they performed the ritual, so that it not only entertained their listeners, but also served as a serious instrument of healing.